2006
DOI: 10.1080/07434610500387540
|View full text |Cite
|
Sign up to set email alerts
|

AAC menu interface: Effectiveness of active versus passive learning to master abbreviation-expansion codes

Abstract: This study investigated the accuracy with which 30 young adults without disabilities learned abbreviation expansion codes associated with specific vocabulary items that were stored in an AAC device with two accessing methods: mouse access and keyboard access. Both accessing methods utilized a specialized computer application, called AAC Menu, which allowed for errorless practice. Mouse access prompted passive learning, whereas keyboard access prompted active learning. Results revealed that participants who acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The participants’ accuracy in responses significantly improved. The completion time of each test indicated that the organizational pattern, length, complexity of sentences, and word order affect the intervention efficiency (Sigafoos et al 2011 ; Wisenburn and Higginbotham 2008 ; Bruno and Trembath 2006 ; Gregory et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants’ accuracy in responses significantly improved. The completion time of each test indicated that the organizational pattern, length, complexity of sentences, and word order affect the intervention efficiency (Sigafoos et al 2011 ; Wisenburn and Higginbotham 2008 ; Bruno and Trembath 2006 ; Gregory et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wallace et al ( 2010 ), Gregory et al ( 2006 ), and Bruno and Trembath ( 2006 ) studied the effects of image contextualization and verbal prompts on the accuracy and speed of the AAC navigational competence of users. With high- and low-context graphical interfaces at different levels, the users demonstrated significant differences in their cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…"the apple is eaten by john"). Gregory et al (2006) created abbreviation codes (e.g. "rmb" = "remember").…”
Section: Related Workmentioning
confidence: 99%
“…Alguns trabalhos internacionais começam a valorizar o papel da família no processo de inserção desse recurso em sujeitos com limitações orais importantes [2][3][4][5][6][7][8][9] . Entretanto, pode-se observar que os artigos não valorizam a investigação sobre a função materna e a intersubjetividade mãe-lho, mas somente o processo de seleção do recurso (design e acessibilidade) [10][11][12][13] , os aspectos linguísticos 14,15 e foco único no usuário [16][17][18][19] . Em um ensaio teórico com foco na família 2 , foram criados contextos hipotéticos que retratam situações cotidianas na relação comunicacional.…”
Section: Introductionunclassified